Occurrence and removal of PFAS from landfill leachates - Nowak, Rafał (Instal, 2025)
In recent years, there has been growing interest in emerging contaminants (EC), which pose a serious threat to the environment and human health. Among these are per – and polyfluoroalkyl substances (PFAS), anthropogenic compounds characterized by exceptional chemical stability, resistance to degradation, and high environmental mobility. Due to these properties, PFAS are often referred to as “forever chemicals”. This paper reviews the literature on the occurrence of PFAS in landfill leachate. Methods for their removal are presented, and the effectiveness of various leachate treatment technologies is evaluated. The comparison indicates that conventional treatment methods are largely ineffective in removing PFAS, making it necessary to apply additional unit processes and integrated treatment technologies. This is crucial to reducing PFAS emissions into the environment and minimizing their harmful impacts